(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Google Form is a service that makes it easy for users to carry out surveys, creating forms that can be filled out quickly and can immediately see the results of the questionnaire quickly. This online form is based on questions or questionnaires which can be revised by the creators and can also be viewed with diagrams or graphs that are more attractive and easy for everyone to understand. In implementing this community service, the method used is the lecture and discussion method which explains Google Form and its features. The purpose of this service is so that Kuranji Community Health Center staff can apply the use of Google Forms and existing features, because there are still many staff who do not understand Google Forms and the features available on Google Forms. The results obtained from this service are that all Kuranji Community Health Center staff who took part in this socialization were able to understand and use the Google Form application better than before they were given this training. Suggestions for the future include more training related to the use of computers which is directly related to social media, so that the staff of this health center are not left behind by information technology which continues to develop rapidly.